Investigating the Indonesia Folk Song Arrangement in Six Choir Competition, 2019 - Rachel Mediana Untung (Institut Seni Indonesia Yogyakarta, 2020)
This study is aimed at investigating the trend of folk song arrangement in six Choir Competitions Folklore Category, 2019. It is specifically focused on investigating three things: the trend of arrangers’ names, title of, origin of folk songs performed in the competitions, the characteristic of the arrangement and relationship between the arrangers and the national choir competitions committee. The reason of choosing the topic is because such a folk song arrangement is seen to be one of the key factors in conducting a choir competition, folklore category. As for the research method, it is more on music behaviour in a relational teritory. Therefore, it used a document study and qualitative research design. In this case, the researcher observed in six choir competitions and interviewed the arrangers, choir leaders, and musicians taking apart in the competitions. The findings revealed that the most frequently used arrangement was Ken Steven’s “Cikala Le Pong Pong”, the most popular arranger was Budi Susanto Yohanes, and Java and Madura were the two origins from which most of the folk songs were performed in choir competitions. The characteristic of the most popular one due to its unique arrangement in the form of vibrant music rhythm and body percussion. It revealed that an arranger is the first key agent in a systemic social-organization mechanism like in a choir competition.